Pengaruh Kualitas Produk, Harga, Promosi Dan Lokasi Terhadap Minat Beli Kopi Lawoek Temanggung - Fika Fitria Adhistiani; Kemal Budi Mulyono (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine the effect of product quality, price, promotion, and location on consumer purchasing interest. The location used in this study is Kopi Lawoek Temanggung, located on the 2nd floor of Temanggung Indah Shop House, Jl. Kepatihan Tim., Alun-alun, Kec. Temanggung, Kabupaten Temanggung, Central Java 56212. The population in this study is Kopi Lawoek Temanggung consumers. The sampling technique used is Non-Probability Sampling, specifically Purposive Sampling. The sample size was determined using the Lemeshow formula, and this study used 100 samples. Data collection was conducted using the Likert scale. This study employed validity and reliability tests to ensure the validity of the data. This study used descriptive statistical analysis to describe data grouping and multiple regression analysis to determine the influence of each variable. The analysis tool used in this study was IBM Statistical Package for the Social Sciences (SPSS) version 25. The results of this study indicate that there is a partial and simultaneous influence of product quality, price, promotion, and location on the purchasing interest of consumers of Kopi Lawoek Temanggung. Based on the R-squared test, there are 6.2% other factors outside the scope of this study that influence consumer purchase interest. Therefore, to further refine and provide a more specific understanding, future research is encouraged to include moderating variables or intervening variables such as service quality, facilities, and brand trust. Keywords: Product Quality; Price; Promotion; Location; Purchase Interest